2017
DOI: 10.1177/2050640616644392
|View full text |Cite
|
Sign up to set email alerts
|

The expansion of endoscopic submucosal dissection in France: A prospective nationwide survey

Abstract: In this multicenter study, ESD achieved high rates of en bloc resection with a significant trend toward better outcomes over time. Improvements in lesion delineation and characterization are still needed to increase R0 resection rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 21 publications
5
37
2
1
Order By: Relevance
“…A recent nationwide survey from 14 centers in France performing ESD in the UGIT reported a mean procedure duration of 108.2 ± 62 (range of 37 to 330) minutes, en-bloc resection, and R0 rate 91.7% and 71.2%, respectively [19]. In Taiwan, a multicenter case series reported a median procedure duration of gastric ESD of 92.4 minutes for lesions of a median size of 18 mm, with an en-bloc resection rate of 91% [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent nationwide survey from 14 centers in France performing ESD in the UGIT reported a mean procedure duration of 108.2 ± 62 (range of 37 to 330) minutes, en-bloc resection, and R0 rate 91.7% and 71.2%, respectively [19]. In Taiwan, a multicenter case series reported a median procedure duration of gastric ESD of 92.4 minutes for lesions of a median size of 18 mm, with an en-bloc resection rate of 91% [8].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the modest records of procedure duration are indicative of ESD being performed in a low volume setting. The recent large series of ESD in multiple centers in France [19] and a prior study in Nagano [26] suggest that center volume may not necessarily be the sole factor affecting outcomes in ESD. Unlike young Japanese endoscopists who embark on ESD, endoscopists here develop a significant amount of experience in therapeutic endoscopy prior to performing ESD.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, one study [23] reported three cases of ileus and another study [33] described 10 cases of electrocoagulation syndrome. Perforation and bleeding rate were not given in two of the studies [30,32]. In the remaining 13 reports median perforation rate was 7% with a range between 0 and 19% ( Table 1).…”
Section: Complications and Follow-upmentioning
confidence: 99%
“…One study was not included because the R0 resection rate of colorectal ESD could not be determined [22]. Thus, after application of our inclusion and exclusion criteria, 15 European full-text studies of colorectal ESD published between 2007 and 2018 were included in this review (Table 1) [15,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. All these included studies were case series.…”
Section: Literature Searchmentioning
confidence: 99%
“…This becomes evident from studies demonstrating significantly better outcome in the hands of experienced endoscopists irrespective of the Western or Eastern origin. [19][20][21] Data from a large metaanalysis 18 demonstrated that the experience of the center/ operator significantly influenced outcomes of the procedures. Centers performing fewer than two ESDs per month had lower R0 resection rates and higher incidence of adverse events.…”
Section: Endoscopic Submucosal Dissection (Esd)mentioning
confidence: 99%